Cultural and Civilizational Ties between India and China Today - E. P. Shavlay (Концепт: философия, религия, культура, 2021)
From the second half of the 20th century bilateral relations between India and China have not received adequate coverage in domestic and foreign science. India and China, due to the strengthening of their economies and the gradual increase in political weight in the world arena, are increasingly viewed as geopolitical rivals, with the emphasis shifting from their bilateral to regional cooperation. It is notable that there are almost no articles on the cultural and civilizational ties between the countries. First of all, this is due to the limited nature of these contacts determined by a number of geopolitical and historical reasons. The countries separated by the world tallest mountain range developed independently from one another with little interaction between them, and it was not until the second half of the 20th century that these Asian powerhouses established solid relations. The bipolar period, in fact, formed the countries’ ambiguous perception of each other, which in many respects continues to restrain cooperation not only in the cultural sphere, but also in other areas. In addition, China and India themselves tend to pay little attention to this lack of communication, since at this stage and in the context of mistrust and rivalry cultural and civilizational ties are not a priority. Even statistics are scarce in both Indian and Chinese sources. At the same time, it is this line of cooperation that might somewhat smooth out the contradictions that have accumulated between the countries in other areas and contribute to a better understanding of each other. Because of intensifying personal contacts between the citizens of both countries and growing importance of the media sphere this mutual understanding is of utmost importance. This article aims to fill the gap that exists today in the scientific field regarding the dialogue of cultures between Delhi and Beijing. The author examines the main elements of cultural cooperation between the two countries and identifies the key problems they face today, as well as points out the opportunities for rapprochement based on the areas that make possible the development of appropriate interaction: religion, traditional health practices, similarities in the political outlook, large expatriot communities, education, art and tourism.